Trust : self-interest and the common good - Kohn, Marek (Oxford University Press, 2008)
Trust lies at the heart of our relationships, our society and our everyday lives. From fascinating puzzles about the biological origins of trust, to the wider social and political implications of trust in human society, this short but thought-provoking book explores how trust works, what makes it possible, and why it matters more than ever today. - ;Trust - our belief in the truth or reliability of someone or something - lies at the very heart of our relationships, our society and our everyday lives. Much of the time we take it for granted. And yet trust, or the lack of it, is becoming an incr.